Concepts of blood transfusion in adults. - Goodnough, LT; Levy, J; Murphy, M (2013)
Recent progress has been made in the identification and implementation of best transfusion practices on the basis of evidence-based clinical trials, published clinical practice guidelines, and process improvements for blood use and clinical patient outcomes. However, substantial variability persists in transfusion outcomes for patients in some clinical settings--eg, patients undergoing cardiothoracic surgery. This variability could be the result of insufficient understanding of published guidelines; different recommendations of medical societies, including the specification of a haemoglobin concentration threshold to use as a transfusion trigger; the value of haemoglobin as a surrogate indicator for transfusion benefit, even though only changes in concentration and not absolute red cell mass of haemoglobin can be identified; and disagreement about the validity of the level 1 evidence for clinical practice guidelines. Nevertheless, institutional experience and national databases suggest that a restrictive blood transfusion approach is being increasingly implemented as best practice.